Kebijakan Terhadap Anak Berhadapan Hukum - Nur Arifah; Muhtar Said (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Children are a trust and a gift from God Almighty, because within them are already embedded the rights and dignity as complete human beings. In Law Number 11 of 2012 concerning the Juvenile Justice System in conjunction with Law Number 3 of 1977 concerning the Juvenile Court, the term "Child in Conflict with the Law" is defined. In Chapter 1 Article 1 point 2, it is stated that "A Child in Conflict with the Law is a child who is in conflict with the law, a child who is a victim of a crime, and a child who is subject to criminal sanctions." Furthermore, in point 3, it is mentioned that "A Child in Conflict with the Law, hereinafter referred to as a child who is 12 (twelve) years old but not yet 18 (eighteen) years old, who commits a crime.